Aspectos numéricos, morfológicos e mofométricos das comunidades bacterianas em diferentes escalas trófica e temporal, em reservatórios - Racy, Fernando Paulo Pereira (Universidade Federal de São Carlos, 2004)
The morphology and size of bacterial cells taken from three reservoirs in different trophic state (Barra Bonita eutrophic, Broa mesotrophic and Lagoa Dourada - oligotrophic), were analysed through images acquired by epifluorescence microscopy (with DAPI fluorescent stain). In these water-bodies, the relative frequencies were calculated for each bacterial morphotype (coccus, coccobacillus, bacillus, vibrio, filament and spirillum) and biovolume. The relative frequencies of biovolumes and morphotypes were converted into indexes of size diversity (SDI) and morphological diversity (MDI) using the Shannon Index for calculations, and population densities (D) were also estimated. These values were compared with the mean trophic state index (mTSI) calculated for each environment. Among the physical and chemical variables, total phosphorus discriminated most clearly between different trophic states during the studied period, while among biological variables, bacterial population density was the most significant indicator of the trophic state of the environments. The MDI proved to be significantly different between the eutrophic and oligotrophic environments, as well as between the mesotrophic and oligotrophic reservoirs, but not consistently so between the eutrophic and mesotrophic, possibly because of the similarity of the trophic state in the last two. The SDI was found to differentiate significantly between the eutrophic and oligotrophic environments, but not between either of these and the mesotrophic. In the oligotrophic environment there was an extremely significant negative linear correlation (r = - 0.9735, p = 0.001) between mTSI and MDI; this correlation was especially significant with chlorophyll concentration (Chla) but not significant with the other components of the mTSI.
Keywords: Efeitos de aspectos específicos do ambiente sobre os organismos; Bactérias; Morfologia; Morfometria; Estado trófico; Densidade; CIENCIAS BIOLOGICAS::MICROBIOLOGIA